Avaliação experimental da qualidade de enlace de redes de sensores sem fio industriais em instalações ao ar livre - Gomes, Emerson Brasil (2019)
TheWireless Sensor Networks (WSN) have, as the main purpose to gather sensors information, in a pre-defined area, from sensor devices (nodes) that are capable to acquire, process and transmit data. The WSN are applicable in a wide range of fields, including industrial automation, where they can be used for monitoring and control industrial plants. In this application field, there are the Industrial WSN (IWSN) which aim to attend to the specific requirements of the industrial systems, such as communication with high reliability and low latency, which can be affected by the inherent characteristics of wireless communication. Electromagnetic signals can be attenuated, obstructed or propagated through multiple paths, due to hardware and metallic materials, widely used in industrial environments. This work aims to experimentally study the IWSN installed in outdoor industrial environments. The first part of the work consists on the characterization of two industrial plants (one mainly static and another mainly dynamic) with regard to the quality of the radio link in multiple channels. Another objective of the present work is to validate, through an experiment in a third outdoor industrial plant, a Link Quality Estimator (LQE) and also a device (sensor node LQE), which estimates the quality of links in real time, both proposed by Gomes in 2017. In order to guarantee a good quality of service in the IWSN, the obtained results reinforce the importance of the use of adaptive protocols that select the appropriate channels for each link, due to the spatial and temporal variations, which affect the quality of the channels